Periodic solutions of a class of indefinite singular differential equations - Zaitao Liang; Xiuqiang Zhang; Shengjun Li; Ziqing Zhou (Electronic Research Archive, 2023)
In this article, some sufficient conditions for the existence of positive periodic solutions of a more general indefinite singular differential equation are established. The results are applicable to strong singularities as well as weak singularities. Some results in literature are generalized.